2022
DOI: 10.3389/fpain.2022.1085791
|View full text |Cite
|
Sign up to set email alerts
|

Body movement as a biomarker for use in chronic pain rehabilitation: An embedded analysis of an RCT of a virtual reality solution for adults with chronic pain

Abstract: IntroductionChronic low back pain (CLBP) is a major public health problem. Reliably measuring the effects of chronic pain on movement and activity, and any changes due to treatment, is a healthcare challenge. A recently published paper demonstrated that a novel digital therapeutic (DTxP) was efficacious in reducing fear of movement and increasing the quality of life of adult patients with moderate to severe CLBP. In this paper, we report a study of how data from wearable devices collected in this study could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The current selection of studies used heart rate sensors (n = 6) and respiratory sensors (n = 5), with 1 study using a wearable electroencephalogram (EEG) 8 and 1 study using a commercial smart bracelet to detect electrodermal activity. 52…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The current selection of studies used heart rate sensors (n = 6) and respiratory sensors (n = 5), with 1 study using a wearable electroencephalogram (EEG) 8 and 1 study using a commercial smart bracelet to detect electrodermal activity. 52…”
Section: Resultsmentioning
confidence: 99%
“…70,72 A recent virtual reality study using both headset and handheld sensors found changes in movement velocity to be associated with both fear of movement and reinjury and chronic low back pain. 52 This may not be due to slowed movement so much as alternative joint coordination choices 86 and stops and hesitation in movement 94 (associated with fear of movement 39,67,71 ). The relationship between fear and movement detection seems stronger when the fear of movement is measured in relation to the movement task 26,27,38 rather than the total TSK score 38,54 or pain-related anxiety 85 rather than general anxiety.…”
Section: Movement and Activity Monitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…This wearable device is primarily used for research in fields such as psychology, neuroscience, and physiology. It is also used for monitoring stress and emotional states, as well as for tracking sleep patterns and physical activity in chronic pain rehabilitation [ 67 ], and for monitoring opioid use in patients with pain conditions [ 68 ].…”
Section: Neurophysiology-based Pain Detectionmentioning
confidence: 99%